THE CULTURAL VALUES ANALYSIS OF ENGLISH KIDS’ SONGS AT K-APEL MAKASSAR - Tsamratul’aeni Tsamratul’aeni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
English kids song used by the teacher at K-APEL Makassar. The list was consisted of some parts such as title, theme of the songs, the diction by the writer of the songs (diction) and the last is the kinds of cultural values appears in the songs. Culture can be showed by songs and through the songs the students are guided to know the culture from different culture and the students learn more about new vocabularies in songs. It is fun and interesting media for the teacher as educator to explore the ability of students to recognize some cultures. The result of this research shows that the kid songs frequently used by the English teacher at K-APEL Makassar were very various in culture values presented in the songs concluding profession, food, and activities. One of the song there were some positive characters such as a postman who never the status of the customer whether rich or poor. Furthermore, the songs frequently used by the teacher give some cultural knowledge to the students that are really needed by the students.